2018
DOI: 10.1017/s0007114518002738
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk score based on fat mass and obesity-associated, transmembrane protein 18 and fibronectin type III domain containing 5 polymorphisms is associated with anthropometric characteristics in South Brazilian children and adolescents

Abstract: The prevalence of childhood obesity has increased worldwide. Although it is considered a polygenic inheritance disease, little is known about its susceptibility when the additive effect is considered. The aim of this study is to investigate whether the genetic risk score (GRS) based on previously associated obesity polymorphisms (SNP) rs9939609 (fat mass and obesity-associated (FTO)), rs6548238 (transmembrane protein 18 (TMEM18)) and rs16835198 (fibronectin type III domain containing 5 (FNDC5)) could serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
6
0
2
Order By: Relevance
“…Based on different genetic models, the results showed that TT genotype of FNDC5 (rs16835198) increased the risk of overweight or obesity in children and adolescents. Todendi et al 30 reported that TT genotype of FNDC 5 (rs16835198) increased risk of obesity in South Brazilian children and adolescents. The studies showed that the obese adults with TT genotype of FNDC 5 (rs16835198) had higher levels of total cholesterol (TC), triacylglycerol (TG) and low-density lipoprotein (LDL-C), lower levels of high-density lipoprotein (HDL-C).…”
Section: Discussionmentioning
confidence: 99%
“…Based on different genetic models, the results showed that TT genotype of FNDC5 (rs16835198) increased the risk of overweight or obesity in children and adolescents. Todendi et al 30 reported that TT genotype of FNDC 5 (rs16835198) increased risk of obesity in South Brazilian children and adolescents. The studies showed that the obese adults with TT genotype of FNDC 5 (rs16835198) had higher levels of total cholesterol (TC), triacylglycerol (TG) and low-density lipoprotein (LDL-C), lower levels of high-density lipoprotein (HDL-C).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered that the prevention and treatment of childhood obesity is a complex task. Additionally, it is known that this disease is of polygenic origin, and other genes are also associated with it, including MCR4 , LEP , FTO, and TMEM18 [ 14 , 32 ]. Knowing that increasing levels of physical activity is an important part of the process, we should mention mechanisms for promoting a more active lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…This association suggests that FNDC5 is beneficial for the treatment of obesity, diabetes, and a variety of pathological conditions characterized by an imbalance in energy expenditure [ 13 ]. It is observed that the human locus FNDC5 rs16835198 contributed positively to anthropometric phenotypes in a previous Brazilian study [ 14 ]. However, the role of specific components of physical fitness in the relationship between FNDC5 polymorphism and adiposity is not known.…”
Section: Introductionmentioning
confidence: 99%
“…TaqMan™ assays C__29311887_10 (rs6548238), C__30090620_10 (rs9939609) and C__34204885_10 (rs16835198) and Master Mix PCR Universal were purchased from Applied Biosystems. The genetic risk score (GRS) was based on previously associated obesity single‐nucleotide polymorphism (SNP) rs9939609 ( FTO ), rs6548238 ( TMEM18 ), and rs16835198 ( FNDC5 ) 23 . The unweighted GRS was constructed using a genotypic score based on the number of unfavorable alleles (those associated with higher levels of BMI Z‐score and waist circumference) that were carried by each subject for each of the three SNP 24 …”
Section: Methodsmentioning
confidence: 99%